Foundational Research in Accounting: Professional Memoirs and Beyond. - Ijiri, Yuri; Boatsman, James R. (The Accounting Review, 1996)
Abstract Reviews the book `Foundational Research in Accounting: Professional Memoirs and Beyond,' by Richard Mattessich.